2015
DOI: 10.1016/j.seizure.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vagus nerve stimulation on cardiorespiratory parameters during rest and exercise

Abstract: This pilot study shows that VNS causes an increase in breathing frequency and a decrease in tidal volume and heart rate in the majority of patients, during both rest and exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…On the other hand, afferent vagal, A-type and C-type, sensory fibers innervate lung stretch receptors and nociceptors, respectively, and, when stimulated, elicit various changes in breathing rate and pattern 30,45 . Similar changes in cardiac and pulmonary functional parameters in response to cervical VNS have been reported in experimental animals 27,46 and in humans 47 , but this is the first time, to our knowledge, that these responses have been evaluated in the context of vagotomies, providing direct functional evidence for 2 easily obtainable, in experimental animals and in humans, markers of activation by VNS of efferent and afferent vagal fibers, respectively 47 .…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, afferent vagal, A-type and C-type, sensory fibers innervate lung stretch receptors and nociceptors, respectively, and, when stimulated, elicit various changes in breathing rate and pattern 30,45 . Similar changes in cardiac and pulmonary functional parameters in response to cervical VNS have been reported in experimental animals 27,46 and in humans 47 , but this is the first time, to our knowledge, that these responses have been evaluated in the context of vagotomies, providing direct functional evidence for 2 easily obtainable, in experimental animals and in humans, markers of activation by VNS of efferent and afferent vagal fibers, respectively 47 .…”
Section: Discussionsupporting
confidence: 72%
“…Epilepsy type 27,30 , epilepsy duration 27 , seizure type 27 and Vagus Nerve Stimulator (VNS) implant side effects 49 were not considered to be associated with performance. Increased age 27 , lower BMI 27 and being female 40 were associated with improved performance, as measured by physical competence 27 and METs 40 .…”
Section: Exercise/fitness Testsmentioning
confidence: 99%
“…28 Matched controls were used in 11 studies. 27,30,34,35,40,41,43,61,62,64,66 Fourteen studies 26,28,[33][34][35][37][38][39]42,56,57,60,64,65 exclusively used questionnaires, five studies 30,32,36,49,66 exclusively used exercise/fitness tests, and seven studies 40,41,43,44,61,62,67 used both methods of data collection. One study 27 used questionnaires, an exercise/fitness test, and a pedometer.…”
Section: Pa In Pwe Compared To Controlsmentioning
confidence: 99%
“…In fact, VNS may even increase the risk of SUDEP (Annegers et al 1998). VNS has been shown to regulate sympathetic activation of the sinoatrial node (Zhou et al 2016) and reduce resting HR (Mulders et al 2015) and is believed to enhance parasympathetic activity (Kampusch et al 2015). Additionally, VNS is hypothesized to worsen sleepbreathing disorders via altered laryngeal motility (Zambrelli et al 2016) and has been shown to trigger obstructive sleep apnea, a condition often coupled with an overexpression of parasympathetic activity (Ebben et al 2008;Parhizgar et al 2011;Vollono et al 2015).…”
Section: Possible Physiological Mechanismsmentioning
confidence: 99%